Multi-scale investigation in the frequency domain of Ar/HMDSO dusty plasma with pulsed injection of HMDSO. (24th May 2019) - Garofano, V; Bérard, R; Boivin, S; Joblin, C; Makasheva, K; Stafford, L
Abstract: A combination of time-resolved optical emission spectroscopy measurements and collisional–radiative modeling is used to investigate the phenomena occurring over multiple time scales in the frequency domain of a low-pressure, axially asymmetric, capacitively coupled radio-frequency (RF) argon plasma with pulsed injection of hexamethyldisiloxane (HMDSO, Si2 O(CH3 )6 ). The collisional–radiative model developed here considers the population of argon 1s and all ten 2p levels (in Paschen's notation). The presence of HMDSO in the plasma is accounted for in the model by quenching of the argon 1s states by species generated by plasma processing of HMDSO, including HMDSO-15 (Si2 O(CH3 )5 ), acetylene (C2 H2 ) and methane (CH4 ). Detailed analysis of the relative populations of Ar 2p states reveals cyclic evolutions of the electron temperature, electron density and quenching frequency that are shown to be linked to the kinetics of dust formation in Ar/HMDSO plasmas. Penning ionization of HMDSO and its fragments is found to be an important source of electrons for the plasma maintenance. It is at the origin of the cyclic formation/disappearance of the dust cloud, without attenuation of the phenomenon, as long as the pulsed injection of HMDSO is sustained. The multi-scale approach used in this study further reveals the straightforward relation of the frequency of HMDSO pulsed injection, in particular the HMDSO duty cycle, with the frequency of dust formation/disappearance cycle.